2018
DOI: 10.1093/tas/txy111
|View full text |Cite
|
Sign up to set email alerts
|

Association between residual feed intake and enteric methane emissions in Hereford steers

Abstract: The objective of this study was to quantify the emissions of enteric CH4 from growing Hereford steers raised under feedlot conditions based on contrasting levels of residual feed intake (RFI). A repeated measurements experiment was conducted over 20 d to determine CH4 production from two groups of nine Hereford steers, with contrasting RFI values (mean ± SD): low RFI (LRFI group; −0.78 ± 0.22 kg DMI/d) vs. high RFI (HRFI group; 0.83 ± 0.34 kg DMI/d). Steers were selected from a larger contemporary population i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 28 publications
0
7
1
Order By: Relevance
“…Greater reductions in enteric CH 4 emissions (15–30%) were reported in the literature for more efficient taurine animals [ 10 , 13 , 32 ] compared to the reduction of approximately 5% in the emission of zebuine animals classified as negative RFI in the present study ( Table 3 ). Results similar to those of the present study were observed in crossbred taurine heifers and cows classified as more efficient, with a daily CH 4 reduction of 2.5% and 3.7%, respectively, compared to less efficient animals [ 34 ].…”
Section: Discussioncontrasting
confidence: 44%
See 2 more Smart Citations
“…Greater reductions in enteric CH 4 emissions (15–30%) were reported in the literature for more efficient taurine animals [ 10 , 13 , 32 ] compared to the reduction of approximately 5% in the emission of zebuine animals classified as negative RFI in the present study ( Table 3 ). Results similar to those of the present study were observed in crossbred taurine heifers and cows classified as more efficient, with a daily CH 4 reduction of 2.5% and 3.7%, respectively, compared to less efficient animals [ 34 ].…”
Section: Discussioncontrasting
confidence: 44%
“…Some studies evaluating CH 4 emission in animals classified as negative and positive RFI reported differences in emissions per kg of DMI, although they found no differences in CH 4 production [ 30 , 33 ]. However, other studies reported lower CH 4 emissions and lower CH 4 emission per DMI in negative RFI animals [ 29 , 32 ]. One explanation would be a lower particle passage rate in the rumen due to differences in feeding behavior since more efficient animals spend less time feeding and therefore exhibit a higher feeding rate than positive RFI animals [ 19 , 32 ].…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…IRC = indirect respiratory chamber; GF = GreenFeed system (C-Lock Inc., Rapid City, SD, USA). Sources: Dini et al. (2019 ; beef, BW = 357 kg BW; SF 6 ); Hegarty et al.…”
Section: Interrelationships Between Methane Production Dmi and Fcementioning
confidence: 99%
“…Several studies have investigated the use of breeding for lower residual feed intake (RFI) as a way to reduce CH 4 production [93][94][95]. A scenario was conducted modeling feed intake and CH 4 production rates in an Australian beef herd selected for low RFI compared to a national Australian herd for 25 years [96].…”
Section: Breeding For Lower Methane Productionmentioning
confidence: 99%